Determinants of competitive performance in rhythmic gymnastics. A review - Bobo-Arce, M.; Méndez-Rial, B. (Journal of Human Sport & Exercise, 2013)
Rhythmic Gymnastics is as a complex artistic and aesthetic sport with a particular training process and which demands high levels of physical and psychological stress in competition. Not many studies explain a good proposal which determinate the predictors of a competitive performance and a useful interaction-model of training and sport performance for the different context, ages and levels in rhythmic gymnastic. In this perspective, based on a critical examination of the literature about "Rhythmic Gymnastics" and "Performance", the aim of this research was to identify the factors that have been studied to predict a higher performance in Rhythmic Gymnastics, analyze them and determinate an "effectively training proposal" to achieve the higher results in competitions. We divided the references in different groups: a) Physiological and biological condition; b) Technical aspects; c) Psychological factors; d) Training process, e) Other dimensions and f) Performance analysis. The results show that most studies on rhythmic gymnastics are descriptive studies about a topic, fewer studies have examined one or more variables related with the performance and more scarce are the studies that show a global perspective and try to explain the predictor of the level of performance. In conclusion, we found some determinants of a competitive performance in Rhythmic Gymnastics which define our proposal. Further intervention studies and studies on the way of the Metamodel studies, "The theoretical and interaction of training and sport performance", would permit identify the contribution of each factor to the performance and would explain our model on a properly and scientifically way.